Comparative investigation of molecular orientation and charge collection in highly efficient mixed heterojunctions based on three planar-shaped donors and C70. (25th October 2016) - Zheng, Yanqiong; Wang, Chao; Yang, Fang; Zhang, Jing; Chen, Jingzhe; Li, Xifeng; Zhang, Jianhua
Abstract: Three donor materials, namely, tetraphenyldibenzoperiflanthene (DBP), 1, 1′-bis (di-4-tolylaminophenyl) cyclohexane (TAPC), tris[4-(5-phenylthiophen-2-yl)phenyl] amine (TPTPA), and C70 based mixed heterojunctions (MHJs), all demonstrate a significantly high short-circuit current ( J SC ), together with high power conversion efficiency (PCE), even though TAPC and TPTPA are non-absorbing in the visible region. The J SC shows a much larger difference between the C60 MHJs than the C70 MHJs when the same donor is included. The difference between their absorption and photoluminescence spectra is negligible. The 5 wt% DBP blend film shows a more regular morphology, with well-distributed circular grains, than the other two donors. The priority of horizontal orientation is DBP  >  TPTPA  >  TAPC, thus contributing to a higher J SC in DBP MHJ. The DBP MHJ device also demonstrates superior charge collection efficiency, hole mobility, and stability to the TAPC and TPTPA MHJs.